2019
DOI: 10.5205/1981-8963.2019.242036
|View full text |Cite
|
Sign up to set email alerts
|

Educação permanente como apoio ao PMAQ-AB

Abstract: Objetivo: analisar a educação permanente como apoio para o Programa de Melhoria do Acesso e Qualidade da Atenção Básica em um município de pequeno porte. Método: trata-se de um estudo qualitativo, descritivo e exploratório em que os dados foram provenientes de entrevistas semiestruturadas com 11 profissionais de nível superior, analisados a partir da técnica de Análise de Conteúdo na modalidade Análise Temática Transversal. Resultados: identificaram-se, a partir da análise, como núcleos relevantes: (1) Conheci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
0
0
1
Order By: Relevance
“…These findings corroborate a study 4 performed with dental surgeons, which showed that PHE actions are important for the training of professionals and effective in the daily life of the health service, contributing to their performance in the face of the demands of the service. On the other hand, a research with higher education professionals 3 showed that PHE actions have not collaborated significantly to the change in practice, presenting scarce results incapable of modifying the reality of the service.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings corroborate a study 4 performed with dental surgeons, which showed that PHE actions are important for the training of professionals and effective in the daily life of the health service, contributing to their performance in the face of the demands of the service. On the other hand, a research with higher education professionals 3 showed that PHE actions have not collaborated significantly to the change in practice, presenting scarce results incapable of modifying the reality of the service.…”
Section: Discussionmentioning
confidence: 99%
“…The spaces of PHE are appropriate for the problematization and elaboration of new ways of caring, favoring the change of the work practice of professionals, making them critical and reflective and promoting qualified care. However, obstacles are still present, such as the difficulty in understanding its concepts and the performance of actions disconnected from the practical reality of the service [3][4][5][6][7][8][9][10][11][12][13][14] .…”
mentioning
confidence: 99%
“…A EPS tem como ponto de partida a aprendizagem significativa, que na perspectiva ausubeliana pode ser entendida como aquela que emerge do conhecimento prévio do educando, em que esses conhecimentos funcionam como âncoras (ideiaâncora) de sentidos e significados para auxiliar a construção de novos conhecimentos e novos aprendizados. Essa aprendizagem significativa proposta pela EPS tem como objetivo a transformação da realidade local, das práticas profissionais e da organização do trabalho em saúde (Brasil, 2004;Moreira, 2010;Assis & Mischiat, 2017;Almeida et al, 2019).…”
Section: Relato De Experiênciaunclassified